Understanding Conditionals in the East: A Replication Study of Politzer et al. (2010) With Easterners - Nakamura, Hiroko; Shao, Jing; Baratgin, Jean; Over, David E.; Takahashi, Tatsuji; Yama, Hiroshi (Frontiers in Psychology, 2018)
The new probabilistic approaches to the natural language conditional imply that there is a parallel relation between indicative conditionals “if s then b” and conditional bets “I bet 1 that if s then b” in two aspects. First, the probability of an indicative conditional and the probability of winning a conditional bet are both the conditional probability, P(s|b). Second, both an indicative conditional and a conditional bet have a third value “void” (neither true nor false, neither wins nor loses) when the antecedent is false (¬s)Second, cases in which the antecedent of the conditionals is false (¬s) do not make indicative conditionals true nor false, and are not winning or losing outcomes for conditional bets. These aspects of the parallel relation have been found in Western participants. In the present studies, we investigated whether this parallel is also present in Eastern participants. We replicated the study of Politzer et al. (2010) with Chinese and Japanese participants and made two predictions. First, Eastern participants will tend to engage in more holistic cognition and take all possible cases, including ¬s, into account when they judge the probability of conditional: Easterners may assess the probability of antecedent s out of all possible cases, P(s), and then may focus on consequent b out of s, P(b|s). Consequently, Easterners may judge the probability of the conditional, and of winning the bet, to be P(s) * P(b|s) = P(s & b), and false / losing the bet as P(s) * P(¬b|s) = P(s & ¬b). Second, Eastern participants will tend to be strongly affected by context, and they may not show parallel relationships between indicative conditionals and conditional bets. The results indicate no cultural differences in judging the false antecedent cases: Eastern participants judged false antecedent cases as not making the indicative conditional true nor false, and as not being winning or losing outcomes. However, there were cultural differences when asked about the probability of a conditional. Consistent with our hypothesis, Eastern participants had a greater tendency to take all possible cases into account, especially in conditional bets. We discuss whether these results can be explained